APLIKASI MINYAK ATSIRI SEBAGAI ANTIKAPANG PADA KECAP IKAN YANG DIPRODUKSI DENGAN BROMELIN - , RAHMAYANI DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research was to determine the effective concentration of clove and cinnamon oils which could be applied on fish sauce. The research was carried out by mixing the clove oil and cinnamon oil on the fish sauce in various concentrations. The concentration of clove oil and cinnamon oil applied on fish sauce was based on MIC (Minimum Inhibitor Concentration) test. MICâs values of clove oil toward identified fungal (Aspergillus) were 0,16% and it could not be homogenous when mixed with fish sauce, so it could not be used. MICâs values of cinnamon oil toward identified fungal (Aspergillus) was 0,005% and it could be homogeneous when mixed with fish sauce, so the cinnamon oil could be used. The concentration of cinnamon oil which mixed with fish sauce were 0,005%